2009
DOI: 10.1016/j.ijsolstr.2009.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of residual stresses on the crack-tip constraint in a modified boundary layer model

Abstract: a b s t r a c tResidual stresses play a crucial role in structural integrity assessment. In this study, a large cracked cylinder with a weld in the center is applied to investigate the effect of residual stresses on the cracktip constraint. A modified boundary layer model with a remote displacement-controlled elastic K-field and T-stress under small scale yielding has been used to simulate the problem. A two-dimensional tensile residual stress field due to the weld is introduced into the model by the so-called… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…Cleavage fracture toughness exhibits a strong sensitivity to the local stress and deformation fields due to its highly localized character. Residual stresses affect both the crack driving forces and crack tip constraint, 1,3,4,6 which may further influence the cleavage fracture toughness. Therefore, the effect of residual stresses on cleavage fracture toughness was investigated in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cleavage fracture toughness exhibits a strong sensitivity to the local stress and deformation fields due to its highly localized character. Residual stresses affect both the crack driving forces and crack tip constraint, 1,3,4,6 which may further influence the cleavage fracture toughness. Therefore, the effect of residual stresses on cleavage fracture toughness was investigated in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Residual stresses associated with welding are unavoidable and play an important role in structural integrity of engineering components. It has been shown that the residual stresses influence both the crack driving force 1 and crack‐tip constraint 2–4 . Crack‐tip constraint arises from differences in the level of opening stress near the crack tip and affects the transferability of material toughness, which is a key issue in application of fracture mechanics to assess the integrity of structural components 5 .…”
Section: Introductionmentioning
confidence: 99%
“…11. A negative Q means that the hydrostatic stress is reduced in comparison with the HRR field and the constraint level is low while a positive Q represents that the hydrostatic stress is higher and the constraint level is high [36,39]. It can be observed that the tendency of the Q with the C * is similar as the different r values are employed.…”
Section: * -Q Two Parameter Approachmentioning
confidence: 97%
“…In all fracture surfaces, mainly on actual reel-lay condition and more severe than actual conditions, the results indicate a ductile behavior of WM and HAZ regions. Some works in the literature studied the influence of external loading combined with residual stresses originated from welding procedures on the crack tip stress field (Ref [24][25][26]. They show that the effect of residual stresses becomes negligible at high external loads due to the resulting decrease of the crack tip constraint induced by the residual stresses.…”
Section: Structural Damagementioning
confidence: 99%